MANAGEMENT OF MOSQUE-OWNED ENTERPRISES: STUDY OF NURUL ISLAM MOSQUE MANAGEMENT - Fitra Diansyah, Dimas; Arrumaisyah, Annisa (International Journal of Cultural and Social Science, 2025)
The Mosque-Owned Business Entity (BUMM) is one form of implementing the mosque's imarah function, oriented towards empowering the community's economy through the management of assets and productive businesses based on Islamic values. This research aims to describe the management system of the Mosque-Owned Business Entity (BUMM) at Nurul Islam Mosque and to examine efforts to integrate digitalization aspects in supporting the sustainability and effectiveness of management. The method used in this study is a qualitative approach with data collection techniques through structured interviews, observation, and documentation. Data is analyzed narratively through the processes of data reduction, data presentation, and conclusion drawing in accordance with the field phenomenon analysis flow. The study results indicate that the professional and digital-based management of BUMM can enhance transparency, efficiency, and business competitiveness, although it still faces challenges in technology utilization and human resources.